ÓZBEKSTAN RESPUBLIKASÍNDA XALÍQTÍ HÁM AWÍL XOJALÍǴÍN DIZIMGE ALÍWDÍŃ ÁHMIYETI - Utepova, G.B.; Eshiniyazov, B.A. (SCIENCE and SOCIETY, 2026)
This article discusses the importance of population and agricultural census in public administration. The main goal of the research is to substantiate the role of these registration processes in socio-economic planning. Statistical and comparative analysis methods were used in the research process. As a result, it is determined that the census of the population and agriculture plays an important role in the territorial development of the country, the effective use of resources, and the formation of state policy.